2023
DOI: 10.1371/journal.pwat.0000092
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of Fe-amended biochar for phosphorus removal and recycling from wastewater

Abstract: Using biochar to remove phosphorus (P) from wastewater has the potential to improve surface water quality and recycle recovered P as a fertilizer. In this research, effects of iron modification on P sorption behavior and molecular characterization on two different biochars and an activated carbon were studied. A biochar produced from cow manure anaerobic digest fibers (AD) pyrolyzed under NH3 gas had the greatest phosphate sorption capacity (2300 mg/kg), followed by the activated carbon (AC) (1500 mg/kg), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 106 publications
0
12
0
Order By: Relevance
“…Using Fe for BC modifications is often promoted because Fe is relatively inexpensive and increases the sorption capacity of the BC, making it more suitable for P and micropollutant removal from wastewater (Kearns et al, 2021; Nobaharan et al, 2021; Psaltou et al, 2022). Molecular analysis via XANES spectroscopy and scanning electron microscopy of P sorbed on Fe‐modified BC produced in pyrolysis of coniferous forest biomass showed that the P existed in the BC as Ca‐P species and adsorbed on iron oxides (Strawn et al, 2023). Calcium likely occurs from Ca released from Ca carbonates in the ash fraction of the BC and reacts with phosphate to form Ca‐phosphate minerals with relatively low solubility.…”
Section: Resultsmentioning
confidence: 99%
“…Using Fe for BC modifications is often promoted because Fe is relatively inexpensive and increases the sorption capacity of the BC, making it more suitable for P and micropollutant removal from wastewater (Kearns et al, 2021; Nobaharan et al, 2021; Psaltou et al, 2022). Molecular analysis via XANES spectroscopy and scanning electron microscopy of P sorbed on Fe‐modified BC produced in pyrolysis of coniferous forest biomass showed that the P existed in the BC as Ca‐P species and adsorbed on iron oxides (Strawn et al, 2023). Calcium likely occurs from Ca released from Ca carbonates in the ash fraction of the BC and reacts with phosphate to form Ca‐phosphate minerals with relatively low solubility.…”
Section: Resultsmentioning
confidence: 99%
“…The addition of biochar provides another means to treat wastewater since reactive filtration with metal salts may not remove micropollutant contamination to sufficiently low levels (Baker et al, 2023). Alternately, Fe-modified biochar addition can present an engineered reactive substrate targeted to P adsorption (Strawn et al, 2023). The influent water then enters the reactive sand filter 1 where an airlift assembly continuously moves sand particles to a washbox.…”
Section: Reactive Filtration Process With Biocharmentioning
confidence: 99%
“…Recycling and reusing P to address water pollution, eutrophication of aquatic ecosystems, and soil fertility can supplement limited global reserves of phosphate rock (Carpenter, 2008;Cordell et al, 2009;Yanhui Dai et al, 2023;Glibert, 2020;Lim et al, 2022;Reijnders, 2014;Schindler et al, 2016;Jianlong Wang, Chu, et al, 2020). Adsorption of P moieties onto native and chemically modified biochar is an increasingly studied approach for the removal and recovery of P from wastewaters (Strawn et al, 2023). Biochar from forestry and agricultural green waste is a promising resource for carbon sequestration because it can lock carbon in soils for years, magnifying its ability to be engineered to adsorb P for use as a soil amendment (Lehmann & Joseph, 2015;Möller & Strawn, 2019;Weber & Quicker, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Although RF with catalytic oxidation has a proven ability to remove more than 90% of total phosphorus to ultralow levels (>0.050 mg/L), addition of biochar in this process allows for nutrient recovery through adsorption on an engineered biochar surface as well as providing enhanced catalytic activity (Mohan et al, 2022;Möller & Strawn, 2019;Strawn et al, 2023;Yao et al, 2013;Yu et al, 2023). The application of phosphorus-upcycled biochar as a soil amendment has several environmental benefits further discussed in this paper.…”
Section: Introductionmentioning
confidence: 99%
“…This versatile system has demonstrated capability for very high oxidation potentials and contact times suitable for sterilization (Baker et al, 2023). Recent work with injection of biochar into the process stream with and without ozone demonstrates the removal and recovery of phosphorus in the postsecondary treatment municipal water producing a nutrient-upcycled biochar soil amendment capable of sequestering atmospheric carbon (Strawn et al, 2023;Yu et al, 2023).…”
Section: Introductionmentioning
confidence: 99%